Parental Involvement and Peer Group Influence as Determinants of Students Scholastic Achievement: A Survey of Kwara-North Senatorial District Public Secondary Schools, Nigeria - Atunde, Martins; Medupin, Johnson; Tijani, Abdulganiyu; Sunday, Olaifa; Onyeukwu, Anulika; Ogbundikpa, Ijeoma (Universitas Negeri Surabaya, 2022)
This study examined parental involvement and peer group influence as determinants of students’ scholastic achievement in public secondary schools in Kwara-North Senatorial District of Kwara State, Nigeria. The descriptive research of an ex-post facto type of design was espoused for the study. Multi-stage sampling was used to select 1,428 research participants for the study. Data were collected with the use of structured and validated (r = 0.88) instruments titled: “Parental Involvement and Peer Group Influence Assessment Questionnaire” (PIPGIAQ) and “Students Scholastic Achievement Proforma” (SSAP). Statistical tools like frequency counts, percentage, mean, standard deviation, Pearson Product Moment Correlation statistics and multiple regression analysis were applied appropriately. Finding revealed that, the overall level of parental involvement in schooling (GM = 2.53), and peer group influence (GM = 2.75) dimensions in public secondary schools in Kwara-North Senatorial District were moderate, even as the level of scholastic achievement among public secondary school students was fair (54.5%) too. Also, the study established that parental involvement and peer group influence both contributed 55.4% (R = .554) to students scholastic achievement in public secondary schools in Kwara State, Nigeria.